Exploring Rural Youth Aspirations in Agriculture and role of information Technologies - Muhammad Iftikhar; Muhammad Furqan Khan; Ahsan Ali; Muhammad Saad Faiz; Muhammad Awais; Muhammad Saleem* (Social Science Review Archives, 2025)
Agriculture remains a crucial sector for rural youth; however, their engagement and information-seeking behavior significantly impact agricultural sustainability. This study was designed to explore the aspirations of rural youth in agriculture and the role of information technologies in their engagement. The research was conducted in District Khanewal, Pakistan, to assess their interest in agriculture, sources of agricultural information, satisfaction with these sources, and the challenges they face. A total of 60 young farmers were selected from four randomly chosen union councils of Tehsil Kabirwala. Data were collected through a structured interview schedule. Findings revealed that a majority (68.3%) of respondents preferred agriculture over other occupations, with 73.3% demonstrating an innovative approach by adopting modern farming techniques. Farmers primarily relied on self-experience (mean = 2.78) and YouTube channels (mean = 2.43) for agricultural knowledge, while formal sources such as agricultural officers (mean = 1.95) and websites (mean = 1.45) were used less frequently. Satisfaction levels followed a similar pattern, with self-experience (mean = 2.68) and fellow farmers (mean = 2.30) being the most trusted sources. Key challenges included financial constraints (mean = 4.10), economic problems (mean = 3.87), and policy-related issues (mean = 3.78). Limited access to irrigation (mean = 3.68) and modern technology (mean = 3.67) also hindered agricultural productivity. The study suggests strengthening digital platforms with expert-led content, enhancing the role of extension services, and integrating formal and informal information sources to improve agricultural knowledge dissemination. Addressing financial and infrastructural barriers can further encourage youth participation in agriculture, ensuring sustainable rural development